`Good' Outcomes - Morten Krogh Petersen (Copenhagen Business School (CBS), 2011)
`Good' Outcomes – Handling Multiplicity in Government Communication This thesis examines how five Danish government organizations produce and assess communicative solutions in practice, and argues that government communication may be understood as a case of multiplicity. In the practices of producing and assessing communicative solutions it is uncertain what constitutes a `good' outcome of government communication. This uncertainty is grasped by drawing upon analytical resources from the field of multiplicity-oriented ANT analyses. Empirically, the thesis is based on ethnographic fieldwork conducted at the five government organizations. Combining empirical observations, theoretical insights, and political programmes, four `modes of ordering' are developed and these are utilized in exploring how the multiplicity of government communication unfurls and how it is handled in practice. The thesis shows how the ordering attempts described by the four modes of ordering coexist and interfere, and it suggests the notions of `sequencing' and `singularizing' for understanding how the multiplicity of government communication is handled in the production and assessment of communicative solutions. The study upon which the thesis reports has been carried out in connection with a larger Industrial PhD project, entitled Measurements you can learn from, that aimed at developing, testing, and implementing new and better communication measurements.
hdl:10398/8306
Keywords: 650